PENGELOLAAN BADAN USAHA MILIK DESA BERBASIS MODAL SOSIAL DAN EKONOMI ISLAM DALAM PENGENTASAN KEMISKINAN DI KECAMATAN PONDOK KUBANG - Harmiati Harmiati; Asmara Yumarni (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2019)
The research aims at exploring social capital and Islamics norms as determinants factors in developing Village Economic Enterprises. The research used descriptive quantitative methodology with interviews, observation, and documentation as the tools of data collection. Several findings in the resecarh as mentioned below are : (1) Village Economic Enterprises were founded in 2016 and three of them were restructured in the year of 2017.(2) The Social Capital in the form of Bounding Social Capital is relatively bounded strongly in three villages; Tanjung Terdana, Harapan Makmur, and Tanjung Dalam where the research took place. The Board of Village Economic Enterprises and village community had intensive interaction, support each other to perform communication and coordination. It grows mutual trust among them.(3) The form of Bridging social capital is identified in the community of Taba Jambu Village, where interaction happened in low intensity. Taba jambu Village consists with multietnics group, interaction happes only in occasion of paying the bill of electricity, clean water account, internet account,etc. (4) Linking social capital is identified in the activity of interaction and communication ofVillage Economic Enterprises boards with instructor and enterpreuner. The activity is due to train and to market the product of Calamancy Orange Juice, Calamancy Parfume and Bamboo coal. The Economic activity is occured because of Village Economic Enterprises boards have network beyond the village. The network includes horizontal and vertical network that support the enterprises. (5) Several activities of Village Economic Enterprises namely ; Pos Pay, Home Industri, and renting money, are still contadicticted with islamic syariah(norms). The guidance ( Village regulation or enterprises regulation) is not formulated yet